Adopting Indonesian Folklore as an Instructional Media Through Cards Games - Komang Redy Winatha; Ni Putu Suci Meinarni; Ayu Gede Willdahlia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
Psychologically, humans tend to love games compared to learning. Therefore, learning should be delivered through fun ways and not boring just like a game. This research aims to develop card games as learning media of Interpersonal Skill Course at STMIK STIKOM Indonesia. This course was chosen based on the availability of minimum teaching materials, the level of material abstractness which is high enough, and there is still no innovative learning that can support the learning. Beside easing the students in comprehending the materials of Interpersonal Skill through fun ways, this card game at once also reminds the students about deep philosophy contained in Indonesian folklores. The chosen folklores cover the stories developing and frequently told in the society such as Timun Emas, Malin Kundang, and so on. The research design used research and development method referring to ADDIE model which is limited until the developing stage. The result of this research is learning media the card game which is an innovation in learning process replacing conventional learning. Based on the results of expert test conducted, the learning media in the form of card games adopting Indonesian folklores is valid and successfully developed.